Environmental Education Book Using Plant Classification in TAHURA Ir. H. Juanda for Autistic Children with Emotion Recognition Challenges - meta, nisrina; fara emilia zeni; berlyanessha, azra; izzati fauziyah, zarin nurul; mahadewi devara p., anak agung s.m. (Cendikia: Jurnal Pendidikan dan Pengajaran, 2025)
Abstract Environmental education is crucial for fostering ecosystem awareness, especially for autistic children who struggle with recognizing and managing emotions. Autistic children often interpret emotional and social cues differently, making it difficult to understand and control their own emotions, as well as those of others. This study aims to develop an environmental education book that combines plant classification in Taman Hutan Raya (TAHURA) Ir. H. Juanda with methods to help autistic children recognize and manage emotions. The book uses the natural environment as a living laboratory, encouraging children to observe and classify plants while providing tools to enhance emotional and social skills through simple language and engaging illustrations. This structured approach aligns with the comfort autistic children find in predictability, offering a meaningful and supportive learning experience. The research involves qualitative methods, including in-depth observations, expert interviews, and tests with a small group of autistic children. Preliminary findings indicate significant improvements in learning interest, environmental understanding, and emotional expression. Thus, the book serves as an effective tool not only for environmental education but also for supporting the social and emotional development of autistic children, potentially reducing anxiety and undesirable behavior.